Aplikasi metode box-jenkins dalam kajian pola data runtun waktu produksi teh (Camellia sinensis)=The Box-Jenkins method aplication on studying of time series data pattern of tea production - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK The experiment was conducted in PT Pagilaran, Batang. The experimental data were secondary data recorded from six blocks namely Garjito I, Kebunjati n, Pecundukan II, Sukowero, Sijanggel and Keteleng. Collecting data was done step by step since December 1998 until March 1999. Setting the model! for marginal productivity (MP) and average productivity (AP) time series was based on Box-Jenkins method or ARIMA modell which had three stages i.e. identification, estimation and diagnostic test. Based on the tested model, forecasting had been done to determine when the crossing area between MP graphic and AP graphic would be in which the tea pruning should be done. There were two blocks namely Kebunjati II and Pecundukan II which had done too early pruning (the 58th month). Based on the forecasting the tea pruning should be done at the 61st month for Kebunjati II and at the 63rd month for Pecundukan II. Meanwhile, for the blocks which had not prunned the tea yet there was a recommendation to prun the tea at the 58th month for Sukowero, at the 61st month for Sijanggel and at the 48th month for Keteleng.